Effect of Company Growth, Debt Policy, Dividends, and Profitability on Company Value - Budi Tri Santoso; Ayumi Rahma; Tubagus Arya Abdurachman (Prodi Manajemen Universitas Pamulang, 2022)
The purpose of this study was to examine the effect of firm growth, debt policy, dividend policy, and profitability on firm value. This research was conducted on property and real estate companies listed on the Indonesia Stock Exchange for the 2016-2020 period. In selecting the sample, purposive sampling technique was used. Hypothesis testing is done by using panel data regression. Based on the test results, it is known that simultaneously the company's growth, debt policy, dividend policy, and profitability have an effect on firm value. Partially, only profitability has an effect on firm value, while firm growth, debt policy, and dividend policy have no significant effect on firm value